Bodipy Derivatives as Triplet Photosensitizers and the Related Intersystem Crossing Mechanisms - Chen, Kepeng; Dong, Yu; Zhao, Xiaoyu; Imran, Muhammad; Tang, Geliang; Zhao, Jianzhang; Liu, Qingyun (Frontiers in Chemistry, 2019)
Recently varieties of Bodipy derivatives showing intersystem crossing (ISC) have been reported as triplet photosensitizers, and the application of these compounds in photocatalysis, photodynamic therapy (PDT), and photon upconversion are promising. In this review we summarized the recent development in the area of Bodipy-derived triplet photosensitizers and discussed the molecular structural factors that enhance the ISC ability. The compounds are introduced based on their ISC mechanisms, which include the heavy atom effect, exciton coupling, charge recombination (CR)-induced ISC, using a spin converter and radical enhanced ISC. Some transition metal complexes containing Bodipy chromophores are also discussed. The applications of these new triplet photosensitizers in photodynamic therapy, photocatalysis, and photon upconversion are briefly commented on. We believe the study of new triplet photosensitizers and the application of these novel materials in the abovementioned areas will be blooming.